NAFTA refugees as protagonists: mexican migrant workers take on the fast food giants - Barndt, Deborah (Revista de Estudos e Pesquisas sobre as Américas, 2009)
<span style="font-size: 11.0pt; font-family: ";Calibri";,";sans-serif";; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ";Times New Roman";; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Where does our food come from? Whose hands have planted, cultivated, picked, packed, processed, transported, scanned, sold, sliced, and cooked it? What production practices have transformed it from seed to fruit, from fresh to processed form? Who decides what is grown and how? What are the effects of those decisions on our health and the health of the planet?